Draft Genome Sequence of Aeromonas hydrophila TN97-08 - Tekedar, Hasan C. (Genome Announc, 2016)
Aeromonas hydrophila is an opportunistic pathogen residing in freshwater environments that causes infection in fish and mammals. Here, we report the draft genome sequence of A. hydrophila strain TN97-08 isolated from a diseased bluegill (Lepomis macrochirus) in 1997.